2013
DOI: 10.1002/tesq.125
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Experience Abroad and Language Proficiency on Language Learning Anxiety

Abstract: This study aims to investigate the effect of experience abroad and second language proficiency on foreign language classroom anxiety. Particularly, this study is an attempt to fill the gap in the literature about the affective outcomes after experiences abroad through the anxiety profiles of Korean learners of English as a foreign language (EFL) while taking second language (L2) proficiency into account. Of particular interest was the analysis of an emerging theme in the second language acquisition literature:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 56 publications
(75 reference statements)
4
47
0
1
Order By: Relevance
“…Additionally, when one has more language learning experiences, the tolerance for ambiguity becomes greater. (746) Also with regards to fear of ambiguity (F4), Thompson and Lee (2014) found that a combination of Experience Abroad (EA) and EP are almost equally important, although it was not the case for the other three factors. In other words, for F1 (English class performance anxiety), F2 (lack of self-confidence in English), and F3 (confidence with native speakers of English), the proficiency level outweighed the importance of EA insofar as anxiety was concerned, whereas for F4 (fear of ambiguity), 'EA is crucial to overcome a fear of ambiguity in language learning' (270) as EA and EP both have relatively equal roles in determining the tolerance for ambiguity of the language learners.…”
Section: Anxiety and Multilingualismmentioning
confidence: 93%
“…Additionally, when one has more language learning experiences, the tolerance for ambiguity becomes greater. (746) Also with regards to fear of ambiguity (F4), Thompson and Lee (2014) found that a combination of Experience Abroad (EA) and EP are almost equally important, although it was not the case for the other three factors. In other words, for F1 (English class performance anxiety), F2 (lack of self-confidence in English), and F3 (confidence with native speakers of English), the proficiency level outweighed the importance of EA insofar as anxiety was concerned, whereas for F4 (fear of ambiguity), 'EA is crucial to overcome a fear of ambiguity in language learning' (270) as EA and EP both have relatively equal roles in determining the tolerance for ambiguity of the language learners.…”
Section: Anxiety and Multilingualismmentioning
confidence: 93%
“…Foreign language courses, no matter whether online or offline, necessarily involve oral interactions among peers. Therefore, online foreign language learning anxiety did not present significant differences from its counterpart in the classroom [49,50]. In this respect, the FLCAS developed by Horwitz et al [46] provided us with a simple way to quantify online foreign language learning anxiety.…”
Section: Learning Anxiety and Self-regulation In Language Learningmentioning
confidence: 96%
“…Dewaele (2013b) found a highly significant effect of frequency of use of a FL on FLA in that language: A higher general frequency of use of the L2, L3, L4 or L5 corresponded to lower levels of FLA experienced by 1453 adult multilinguals in these languages with various types of interlocutors in various situations. Thompson and Lee (2014) also reported that 148 Korean EFL students who had studied abroad were less anxious in the English FL classroom after their return. Frequency of use and self-perceived proficiency are different measures, but they are probably influencing each other.…”
Section: Frequency Of Use Of the Flmentioning
confidence: 98%